MEDIA SOSIAL SEBAGAI RUANG PUBLIK ANTARA NETIKET DAN NETIZE - Sri Ayu Astuti (Universitas Muhammadiyah Sidoarjo, 2013)
Form of communication that thrives on social media, users or citizens of social media termed as netizen were not wise enough in using their language style so that it causes the ethical problems of communication. The problem of communication ethics that began in cyberspace continues to be legal issues and many disputing parties choose to solve the problems of communication ethics violations into the legal issues in the realm of justice. Social media as new media is also called as the fifth pillar of democracy as deemed able to perform the functions of the mainstream media and even correct the existence of the mainstream media which has the force of law and untouchable. And there is none of the institutions that belong to third pillar of democracy is dare to correct. It is different with social media as the fifth pillar of democracy, where the social media people are very observant and decisive in response to the mistakes of the mainstream media. The watch dog function, has now moved to citizens social media with massive in the quiet room attractively run the control in various aspects of people’s real life. The world of taboo to correct the mistakes of the mainstream media has now become a reality in one attitude and one word to enforce the truth.